The fantastic flying books of Mr. Morris Lessmore - Joyce, William, 1957-; Bluhm, Joe, 1980- (New York : Atheneum Books for Young Readers, 2012)
Morris Lessmore loves words, stories and books, and after a tornado carries him to another land, dreary and colorless, he finds a single book in color that leads him to an amazing library where, he learns, the books need him as much as he needs them.
"the story that inspired the Academy Award winning short film"
Elementary Grades.
650
AD650L
Decoding demand: 90 (very high) Semantic demand: 94 (very high) Syntactic demand: 93 (very high) Structure demand: 83 (very high)
Accelerated Reader AR
Keywords: Books and reading -- Juvenile fiction; Libraries -- Juvenile fiction; Books and reading -- Fiction; Libraries -- Fiction; Fantasy